Towards a Multi-Stakeholder Approach to Barley Breeding in Ethiopia: Integrating Gender-Specific Preferences - Najjar, Dina; Tsige Abebe, Meseret; Oueslati, Dorsaf; Zeleke, Muluken; M. Oumer, Ali; Sanchez-Garcia, Miguel; Frija, Aymen; Wamatu, Jane (2024)
Barley is a key staple crop in Ethiopia, crucial for food security, malt production, and livestock feed. Smallholder farmers rely heavily on traditional landraces, making them particularly vulnerable to climate change and yield variability (Mohammed et al., 2016; Wada et al., 2022). This study aims to inform trait prioritization for the delivery of high yielding barley genotypes with tolerance to biotic and abiotic stresses, while integrating gender-specific preferences in the breeding process to enhance adoption rates and ensure food security. Women play a pivotal role in agriculture, yet their preferences in seed traits are often overlooked, especially in the Global South (Puskur et al., 2021). This gap leads to the development of crops that do not adequately address the needs of all farmers, particularly in terms of resilience, nutritional quality, and labor requirements (Weltzien et al., 2019; Badstue et al., 2022). The focus of this research is to explore gender-based preferences for seed traits and their implications for agricultural productivity and food security. We attend to the question of what role does a multi-stakeholder approach plays in identifying and incorporating trait preferences for barley varieties, including food and feed traits, to enhance the adoption rates among smallholder farmers in Ethiopia? Our study highlights the importance of incorporating women’s preferences into breeding programs to improve adoption, and benefits, and ensure sustainable agricultural practices.